Flecainide is associated with a lower incidence of arrhythmic events in a large cohort of patients with catecholaminergic polymorphic ventricular tachycardia: original research article - Bergeman, Auke T.; Lieve, Krystien V.V.; Kallas, Dania; Bos, J. Martijn; Rosés i Noguer, Ferran; Denjoy, Isabelle; Zorio, Esther; Kammeraad, Janneke A.E.; Peltenburg, Puck J.; Tobert, Katie; Aiba, Takeshi; Atallah, Joseph; et al. (Circulation, 2023)
BACKGROUND: In severely affected patients with catecholaminergic polymorphic ventricular tachycardia, beta-blockers are often insufficiently protective. The purpose of this study was to evaluate whether flecainide is associated with a lower incidence of arrhythmic events (AEs) when added to beta-blockers in a large cohort of patients with catecholaminergic polymorphic ventricular tachycardia. METHODS: From 2 international registries, this multicenter case cross-over study included patients with a clinical or genetic diagnosis of catecholaminergic polymorphic ventricular tachycardia in whom flecainide was added to beta-blocker therapy. The study period was defined as the period in which background therapy (ie, beta-blocker type [beta1-selective or nonselective]), left cardiac sympathetic denervation, and implantable cardioverter defibrillator treatment status, remained unchanged within individual patients and was divided into pre-flecainide and on-flecainide periods. The primary end point was AEs, defined as sudden cardiac death, sudden cardiac arrest, appropriate implantable cardioverter defibrillator shock, and arrhythmic syncope. The association of flecainide with AE rates was assessed using a generalized linear mixed model assuming negative binomial distribution and random effects for patients. RESULTS: A total of 247 patients (123 [50%] females; median age at start of flecainide, 18 years [interquartile range, 14-29]; median flecainide dose, 2.2 mg/kg per day [interquartile range, 1.7-3.1]) were included. At baseline, all patients used a beta-blocker, 70 (28%) had an implantable cardioverter defibrillator, and 21 (9%) had a left cardiac sympathetic denervation. During a median pre-flecainide follow-up of 2.1 years (interquartile range, 0.4-7.2), 41 patients (17%) experienced 58 AEs (annual event rate, 5.6%). During a median on-flecainide follow-up of 2.9 years (interquartile range, 1.0-6.0), 23 patients (9%) experienced 38 AEs (annual event rate, 4.0%). There were significantly fewer AEs after initiation of flecainide (incidence rate ratio, 0.55 [95% CI, 0.38-0.83]; P=0.007). Among patients who were symptomatic before diagnosis or during the pre-flecainide period (n=167), flecainide was associated with significantly fewer AEs (incidence rate ratio, 0.49 [95% CI, 0.31-0.77]; P=0.002). Among patients with ≥1 AE on beta-blocker therapy (n=41), adding flecainide was also associated with significantly fewer AEs (incidence rate ratio, 0.25 [95% CI, 0.14-0.45]; P<0.001). CONCLUSIONS: For patients with catecholaminergic polymorphic ventricular tachycardia, adding flecainide to beta-blocker therapy was associated with a lower incidence of AEs in the overall cohort, in symptomatic patients, and particularly in patients with breakthrough AEs while on beta-blocker therapy.
Online veröffentlicht: 27. Oktober 2023
Gesehen am 11.04.2024